Do measures of dyadic student–teacher relationships in middle school predict overall student–teacher relationship measures? Not entirely - Virat, Mael; Archambault, Isabelle (Learning environments research, 2025)
Because secondary school students encounter multiple teachers, studies of student–teacher relationships usually measure students' relationships with teachers in general. However, it remains unclear whether these measures reflect students’ relationships with individual teachers. Using a sample of 557 students attending three French middle schools, we investigated whether measures of dyadic student–teacher relationships predict overall student–teacher relationships. To this end, we measured students’ overall relationships with teachers and their relationships with each of their ten core subject teachers, differentiating between the closeness and conflict dimensions of these relationships, while controlling for other important predictors (i.e. behavioral engagement, affective engagement, academic achievement) and taking into account random effects associated with student groups (classes and schools). Overall student–teacher relationships were predicted by dyadic student–teacher relationships only in the case of relationships with teachers of subjects accorded the most class time (French, mathematics, physical education, English). Moreover, dyadic student–teacher relationships and covariates explained only around 50% of the variance of the overall measure, and this was the case for both the conflict and closeness dimensions. These results suggest that overall student–teacher relationships reflect students’ overall school experience but only partly reflect dyadic student–teacher relationships. This finding raises an important question for research on student–teacher relationships: what accounts for the remaining variance in overall relationships? We discuss some explanatory hypotheses.